Identification of a Novel Small Cysteine-Rich Protein in the Fraction from the Biocontrol Fusarium oxysporum Strain CS-20 that Mitigates Fusarium Wilt Symptoms and Triggers Defense Responses in Tomato - Shcherbakova, Larisa A.; Odintsova, Tatyana I.; Stakheev, Alexander A.; Fravel, Deborah R.; Zavriev, Sergey K. (Frontiers in Plant Science, 2016)
The biocontrol effect of the nonpathogenic F. oxysporum strain CS-20 against the tomato wilt pathogen F. oxysporum f. sp. lycopersici (FOL) has been previously reported to be primarily plant-mediated. This study shows that CS-20 produces proteins, which elicit defense responses in tomato plants. Three protein-containing fractions were isolated from CS-20 biomass using size exclusion chromatography. Exposure of seedling roots to one of these fractions prior to inoculation with pathogenic FOL strains significantly reduced wilt severity. This fraction initiated an ion exchange response in cultured tomato cells resulting in a reversible alteration of extracellular pH; increased tomato chitinase activity, and induced systemic resistance by enhancing PR-1 expression in tomato leaves. Two other protein fractions were inactive in seedling protection. The main polypeptide (designated CS20EP), which was specifically present in the defense-inducing fraction and was not detected in inactive protein fractions, was identified. The nucleotide sequence encoding this protein was determined, and its complete amino acid sequence was deduced from direct Edman degradation (25 N-terminal amino acid residues) and DNA sequencing. The CS20EP was found to be a small basic cysteine-rich protein with a pI of 9.87 and 23.43% of hydrophobic amino acid residues. BLAST search in the NCBI database showed that the protein is new; however, it displays 48% sequence similarity with a hypothetical protein FGSG_10784 from F. graminearum strain PH-1. The contribution of CS20EP to elicitation of tomato defense responses resulting in wilt mitigating is discussed.